Detachment of Dunaliella tertiolecta Microalgae from a Glass Surface by a Near-Infrared Optical Trap - Beatriz A. Juarez; Veneranda G. Garces; Beatriz Cordero-Esquivel; Gabriel C. Spalding; Kevin A. O’Donnell (Sensors, 2020)
We report on the observation of the detachment in situ and in vivo of Dunaliella tertiolecta microalgae cells from a glass surface using a 1064 nm wavelength trapping laser beam. The principal bends of both flagella of Dunaliella were seen self-adhered to either the top or bottom coverslip surfaces of a 50 <semantics>μ</semantics>m thick chamber. When a selected attached Dunaliella was placed in the trapping site, it photoresponded to the laser beam by moving its body and flagellar tips, which eventually resulted in its detachment. The dependence of the time required for detachment on the trapping power was measured. No significant difference was found in the detachment time for cells detached from the top or bottom coverslip, indicating that the induced detachment was not due solely to the optical forces applied to the cells. After detachment, the cells remained within the optical trap. Dunaliella detached from the bottom were seen rotating about their long axis in a counterclockwise direction, while those detached from the top did not rotate. The rotation frequency and the minimal force required to escape from the trap were also measured. The average rotation frequency was found to be independent of the trapping power, and the swimming force of a cell escaping the laser trap ranged from 4 to 10 picoNewtons. Our observations provide insight into the photostimulus produced when a near-infrared trapping beam encounters a Dunaliella. The microalgae frequently absorb more light than they can actually use in photosynthesis, which could cause genetic and molecular changes. Our findings may open new research directions into the study of photomovement in species of Dunaliella and other swimming microorganisms that could eventually help to solve technological problems currently confronting biomass production. In future work, studies of the response to excess light may uncover unrecognized mechanisms of photoprotection and photoacclimation.